Infrared spectroscopy: a new diagnostic tool in Alzheimer disease - Griebe, Martin; Daffertshofer, Michael; Stroick, Mark Gregor; Syren, Magdalena; Ahmad-Nejad, Parviz; Neumaier, Michael; Backhaus, Jürgen; Hennerici, Michael G.; Fatar, Marc (Neuroscience letters, 2007)
Biological markers play an evolving role in the diagnosis of Alzheimer disease (AD). We compare conventional measurements of cerebrospinal fluid (CSF) tau and beta-amyloid(1-42) proteins to a novel approach - Fourier transformed infrared (FT-IR) spectroscopy - a simple technique derived from chemical and physical sciences that characterizes intramolecular bonds. For automatic diagnostic analysis, we developed an artificial neural network (ANN). We examined 71 patients with a clinical diagnosis of AD and 66 controls. beta-Amyloid(1-42) was decreased (sensitivity 80% and specificity 78%); tau was elevated (sensitivity 76% and specificity 88%) in CSF of AD patients. The combined tau/beta-amyloid(1-42) quotient was able to distinguish healthy from diseased subjects with 99% sensitivity and 86% specificity. The ANN could separate FT-IR spectroscopy data with 88.5% sensitivity and 80% specificity. FT-IR spectroscopy proved to be cost-effective and simple to perform. Diagnostic sensitivity and specificity is in the range of CSF tau and beta-amyloid(1-42) protein analysis. Larger sample numbers for ANN training and validation could increase diagnostic accuracy and thus prove to be a useful screening tool.